Anemia, insuficiência cardíaca e manejo clínico baseado em evidências - Pereira, Camila Alves [UNESP]; Roscani, Meliza Goi [UNESP]; Zanati, Silméia Garcia [UNESP]; Matsubara, Beatriz Bojikian [UNESP] (Sociedade Brasileira de Cardiologia (SBC), 2013)
Anemia is a prevalent comorbidity and marker of a poorer prognosis in patients with heart failure (HF). Its clinical relevance, as well as its pathophysiology and the clinical management of these patients are important subjects in the specialized literature. In the present review, we describe the current concepts on the pathophysiology of anemia in HF, its diagnostic criteria, and the recommendations for iron supplementation. Also, we make a critical analysis of the major studies showing evidences on the benefits of this supplementation. The four main components of anemia are addressed: chronic disease, dilutional, renal and malabsorption. In patients with HF, the diagnostic criteria are the same as those used in the general population: serum ferritin levels lower than 30 mcg/L in patients without kidney diseases and lower than 100 mcg/L or serum ferritin levels between 100-299 mcg/L with transferring saturation lower than 20% in patients with chronic kidney diseases. Finally, the therapeutic possibilities for anemia in this specific patient population are discussed.

A anemia é uma comorbidade prevalente e marcadora de pior prognóstico em pacientes com insuficiência cardíaca (IC). Sua relevância clínica, bem como a fisiopatologia e abordagem terapêutica nesses pacientes são temas de destaque na literatura especializada. Nessa revisão são descritos os conceitos atuais sobre a fisiopatologia da anemia na IC, os critérios diagnósticos e as indicações da suplementação de ferro, ao mesmo tempo em que são analisados criticamente os principais estudos que ofereceram evidências sobre os benefícios dessa suplementação. São abordados os quatro componentes principais da anemia: doença crônica, dilucional, renal e disabsortiva. Nos pacientes com IC, os critérios para o diagnóstico são os mesmos utilizados na população geral: níveis de ferritina sérica inferiores a 30 mcg/L em pacientes não nefropatas e menores que 100 mcg/L ou ferritina sérica entre 100-299 mcg/L com saturação de transferrina menor que 20% em pacientes com doença renal crônica. Finalmente, são discutidas as possibilidades terapêuticas da anemia nessa população específica de pacientes.
Anemia, heart failure and evidence-based clinical management
Keywords: Deficiência de ferro; Inflamação; Suplementação de ferro; Doença crônica; Doença cardiovascular; Iron deficiency; Inflamation; Iron supplementation; Chronic disease; Cardiovascular disease